Dispute Settlement on E-Commerce Contract: A Practical Analysis of Law - Naziah, Firqotun (Law Research Review Quarterly, 2021)
E-commerce is a form of trade which has its own characteristics that are cross-border trade, not to meet the seller and buyer, use media internet. The birth of Law No. 11 of 2008 is about Information and Electronic Transactions (UU ITE) seems to be the solution to provide protection for consumers. In the IET Law has set the terms validity of e-commerce transactions, establishing the rights and obligations, prohibited acts, responsibility, legal protection, remedies and dispute resolution in e-commerce transactions.